Synthesis and Regularities of the Structure-Activity Relationship in a Series of N-Pyridyl-4-methyl-2,2-dioxo-1H-2λ6,1-benzothiazine-3-carboxamides - Igor V. Ukrainets; Anna A. Burian; Ganna M. Hamza; Natali I. Voloshchuk; Oxana V. Malchenko; Svitlana V. Shishkina; Lyudmila V. Sidorenko; Kateryna O. Burian; Galina Sim (MDPI AG, 2019)
According to our quantum and chemical calculations 4-methyl-2,2-dioxo-1H-2λ6,1-benzothiazine-3-carboxylic acid imidazolide is theoretically almost as reactive as its 2-carbonyl analog, and it forms the corresponding N-pyridyl-4-methyl-2,2-dioxo-1H-2λ6,1-benzothiazine-3-carboxamides with many aminopyridines. However, in practice, the sulfo group introduces significant changes at times and prevents the acylation of sterically hindered amines. One of these products was 2-amino-6-methylpyridine. Thus, it has been concluded that aminopyridines interact with imidazolide in aromatic form where the target for the initial electrophilic attack is the ring nitrogen. To confirm the structure of all substances synthesized, 1H-NMR spectroscopy and X-ray diffraction analysis were used. From X-ray diffraction data it follows that in the crystalline phase the carbonyl and sulfo group may occupy different positions with respect to the plane of the benzothiazine bicycle: this position may be unilateral, typical for 4-methyl-2,2-dioxo-1H-2λ6,1-benzothiazine-3-carboxamides, versatile, and not yet encountered in compounds of this type. A comparison of these data with the results of the pharmacological screening conducted on the standard model of carrageenan inflammation showed that the N-pyridylamides of the first group demonstrated a direct dependence of their analgesic and anti-inflammatory activity on the mutual arrangement of the planes of the benzothiazine and pyridine fragments. The new molecular conformation of the benzothiazine nucleus provides a sufficiently high level of analgesic (but not anti-inflammatory) properties in all N-pyridylamides of the second group with an extremely weak dependence on the spatial arrangement of the pyridine cycle. All substances presented this article proved themselves in varying degrees as analgesics and antiphlogistics. Moreover, two of them—N-(5-methylpyridin-2-yl)- and N-(pyridin-3-yl)-4-methyl-2,2-dioxo-1H-2λ6,1-benzothiazine-3-carboxamides—exceeded the most effective drug of oxicam type Lornoxicam by these indicators.